2018
DOI: 10.1180/clm.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of halloysite (North East Rif, Morocco): evaluation of its suitability for the ceramics industry

Abstract: A halloysite clay from Nador (NE Morocco) was studied to evaluate its suitability in the ceramics industry. A cross-section involving all the Messinian facies was performed in the Melilla Neogene basin, at the foot of the Gourougou volcano, to establish the origin of the halloysite and estimate its reserves. White layers of halloysite and red clays rich in smectite occurring in contact with basal-reef limestone were characterized by mineralogical (XRD, IR), textural (SEM) and physico-chemical analyses (grain-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…2). In addition, a loss on mass of 2.8% occurs at about 100 °C, which is attributed to the loss of the surface adsorbed water [25]. These results indicated that halloysite adsorbs water molecules both on surface and lumen space of the nanotubes.…”
Section: Physicochemical Composition Of Raw Halloysite and Kaolinitementioning
confidence: 85%
See 1 more Smart Citation
“…2). In addition, a loss on mass of 2.8% occurs at about 100 °C, which is attributed to the loss of the surface adsorbed water [25]. These results indicated that halloysite adsorbs water molecules both on surface and lumen space of the nanotubes.…”
Section: Physicochemical Composition Of Raw Halloysite and Kaolinitementioning
confidence: 85%
“…Halloysite is mainly derived from long-term weathering of amorphous silicate, which remained in small amount as relicts associated with raw halloysite [24,25]. Similar to the carbon nanotube, halloysite is of particular importance due to its tubular morphology of 500-1000 nm in length and 10-100 nm in inner diameter [26].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the rolling mechanism of the 1:1 layer of tetrahedral and octahedral sheets, several models have been proposed [6]. Increasing demand for HNT is observed, although it is not as common as kaolinite [7][8][9]. In recent years, several studies have broadened the field of application of HNT to highly technological applications such as catalytic supports and other functional materials due to their particular morphology and specific properties [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing demand for HNT is observed, although it is not as common as kaolinite [7][8][9]. In recent years, several studies have broadened the field of application of HNT to highly technological applications such as catalytic supports and other functional materials due to their particular morphology and specific properties [8,10]. In addition, the nanoparticles are also capable of adsorbing and storing a large number of hydrogen molecules [11] and drugs for controlled release [12][13][14], forming antibacterial biological membranes [15] and polymer-based composites [16][17][18], among other technological uses.…”
Section: Introductionmentioning
confidence: 99%
“…The HNTs are a kind of aluminosilicate clay [Al 2 Si 2 O 5 (OH) 4 .H 2 O with 1:1 layer] with hollow micro and nanotubular structure. Many researchers have worked on halloysite clay characterization . HNTs contain two types of hydroxyl groups, inner and outer hydroxyl groups, which are situated between layers and on the surface of the nanotubes, respectively.…”
Section: Introductionmentioning
confidence: 99%